Dissolved Organic Carbon Along a Meridional Transect in the Western North Pacific Ocean: Distribution, Variation and Controlling Processes - Ge, Tiantian; Luo, Chunle; Ren, Peng; Zhang, Hongmei; Chen, Hongtao; Chen, Zhaohui; Zhang, Jing; Wang, Xuchen (Frontiers in Marine Science, 2022)
Dissolved organic carbon (DOC) in the ocean is one of the largest reduced and exchangeable organic carbon pools on Earth and plays important roles in carbon cycling and biogeochemical processes in the ocean. Here, we report the concentrations and distributions of DOC in water samples collected along a meridional transect in the western North Pacific (NP) Ocean in November 2019. Concentrations of DOC ranged from 33-102 μM, were higher in surface water, decreased rapidly with depth to 1,000 m, and then remained relatively constant. The labile fraction of DOC accounted for 20-40% of the surface bulk DOC and was respired very rapidly in the upper 200 m depth. The semi-labile fraction of DOC accounted for 15-20% of the surface bulk DOC and was exported downward and turned over at water depths of 200-2,000 m. Low concentrations of DOC (33 - 44 μM) were present in the entire water column below 1,000 m along the transect in the NP. Primary production and microbial consumption played major roles in the concentration and distribution of DOC in the euphotic zone, and hydrodynamic mixing and circulation of different water masses appear to be dominant factors controlling the distribution and dynamics of DOC in the deep water of the western NP.